2018
DOI: 10.1007/s00467-018-3929-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and pharmacogenetics of prednisone and prednisolone in patients with nephrotic syndrome

Abstract: Nephrotic syndrome is one of the most common glomerular disorders in childhood. Glucocorticoids have been the cornerstone of the treatment of childhood nephrotic syndrome for several decades, as the majority of children achieves complete remission after prednisone or prednisolone treatment. Currently, treatment guidelines for the first manifestation and relapse of nephrotic syndrome are mostly standardized, while large inter-individual variation is present in the clinical course of disease and side effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 119 publications
0
50
1
7
Order By: Relevance
“…The anti-inflammatory action of the steroids is mediated by two main mechanisms; transactivation and trans-repression (Barnes, 2010a; Schijvens et al, 2019). During transactivation, steroids induce the transcription of anti-inflammatory genes such as lipocortin, and various mitogen-activated protein kinases (Oakley and Cidlowski, 2013) and others.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory action of the steroids is mediated by two main mechanisms; transactivation and trans-repression (Barnes, 2010a; Schijvens et al, 2019). During transactivation, steroids induce the transcription of anti-inflammatory genes such as lipocortin, and various mitogen-activated protein kinases (Oakley and Cidlowski, 2013) and others.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that single daily dosing is as effective as multiple daily dosing in maintaining remission in nephrotic syndrome children [ 33 ]. As part of the limitation of prednisolone in Table 1 , its mode of mechanism to achieve remission of nephrotic syndrome is still unknown [ 34 ]. Various speculations of hypothesis explain the mechanism of prednisolone against MCD patients; most of it went beyond the typical anti-inflammatory or immunosuppressive actions because glomerular inflammation is mostly absent in SSNS [ 34 ].…”
Section: Treatment Options In MCDmentioning
confidence: 99%
“…Genomic mechanisms implicate the activation and/or repression of specific genes encoding anti-and pro-inflammatory proteins. The non-genomic mechanisms of glucocorticoid action remain poorly understood [9]. Polymorphisms of the GR gene (nuclear receptor subfamily three, group C, member 1:NR3C1) are known to be associated with variations in the GR function [10].…”
mentioning
confidence: 99%
“…The activated GR/GC complex exerts its anti-inflammatory and immunosuppressive effects at the nucleus level, directly (via DNA binding) or indirectly (via protein interaction), by decreasing expression of pro-inflammatory genes (transrepression), or increasing expression of anti-inflammatory genes (transactivation). The hypothesis that the anti-inflammatory properties of glucocorticoids are mostly due to transrepression of synthesis of inflammatory mediators, whereas most of their adverse effects are associated with transactivation of genes involved in metabolic processes, led to the development of GR ligands which cause a receptor conformation preferring a GR/protein interaction and not a GR/DNA binding-dependent mechanism, so-called selective glucocorticoid receptor agonists (SEGRAs) [9]. Moreover, GR (but not MR) genetic variations accounted for a significant amount of variance in mean cortisol levels and severity of psychosis or cognitive dysfunction in depression [10].…”
mentioning
confidence: 99%